Samorząd terytorialny w ekonomii instytucjonalne - Jurkowska, Aleksandra; Owsiak, Katarzyna (Local Government in the Institutional Economics, 2009)
The institutional economics focuses on understanding the role of human-made institutions in shaping economic behaviour. On the other hand, new institutional economics is a very different creature politically, but still focuses on the role of institutions in reducing transaction costs. In this context, the main goal of this article is an attempt to formulate the local government unit as the institution e.g. institution of civil society, institutions of local or regional development. Simultaneously, the authors concentrated on the definition of the institution. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 122-129